Application Possibilities of Blockchain in Accounting - Király, Péter Bálint (Public Governance, Administration and Finances Law Review, 2020)
In recent decades technology has advanced rapidly, and inventions that have made our lives easier have emerged. Among the many life changing inventions, Blockchain facilitates our financial activities, for example banking, commerce and accounting, because it eliminates the need for a third party, thus saving us time and money. With its help, we can manage and record asset movements, contracts and their fulfilment, as well as other data by cryptographic methods. In the following article, firstly I will describe the concept and operation of Blockchain and the advantages of using it in the field of accounting. After that I will introduce the accounting principles, based on the Hungarian Accounting Act. Finally, I will address the legal questions raised by applying the accounting principles to Blockchain when they are used in the process of accounting.